Role of tissue expansion in abdominal wall reconstruction: A systematic evidence-based review. Issue 6 (June 2017) - Wooten, Kimberly E.; Ozturk, Cemile Nurdan; Ozturk, Can; Laub, Peter; Aronoff, Nell; Gurunluoglu, Raffi
Summary: Background: Tissue expanders (TEs) can be used to assist primary closure of complicated hernias and large abdominal wall defects. However, there is no consensus regarding the optimal technique, use, or associated risk of TE in abdominal wall reconstruction. Methods: A systematic search of PubMed and Embase databases was conducted to identify articles reporting abdominal wall reconstruction with TE techniques. English articles published between 1980 and 2016 were included on the basis of the following inclusion criteria: two-stage TE surgical technique, >3 cases, reporting of postoperative complications, hernia recurrence, and patient-based clinical data. Results: Fourteen studies containing 103 patients (85 adults and 18 children) were identified for analysis. Most patients presented with a skin-grafted ventral hernia (n = 86). The etiology of the hernia was from trauma or prior abdominal surgery. The remaining patients had TE placed before organ transplantation (n = 12) or for congenital abdominal wall defects (n = 5). The location for expander placement was subcutaneous (n = 74), between the internal and external obliques (n = 26), posterior to the rectus sheath (n = 2), and intra-peritoneal (n = 1). Postoperative infections and implant-related problems were the most commonly reported complications after Stage I. The most common complication after Stage II was recurrent hernia, which was observed in 12 patients (11.7%). Five patients with TE died. Complications and mortality were more prevalent in children, immunosuppressed patients, and those with chronic illnesses. Conclusions: Tissue expansion for abdominal wall reconstruction can be successfully used for a variety of carefully selected patients with an acceptable complication and risk profile.